AN EVALUATION OF TEFL UNDERGRADUATE'S QUESTIONING CLASSROOM ACTIVITIES BASED ON BLOOM'S REVISED TAXONOMY - Cahyaningtyas, Dhestyn Ervina Sigit; Basuki, Yudi; Nurkamto, Joko; Ngadiso, Ngadiso (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Lecturers’ talk during classes stimulates active students, as a means of a successful lecture. This study investigated the levels of questioning used by lecturers. The data, collected from the participants having more than ten year professional experience, were described qualitatively. Observation and interview were used to generate the data. The findings of this study indicated the questions level based on Bloom’s revised taxonomy. Mostly used was the low and middle order thinking, less encouraging students’ critical thinking. Noted 66 questions or about 73% of the total question belong to low order. 22 questions or 25% of all were included medium order. The rest of them, the least of all, 2 questions or equally to 2% were high order. Thus, students and lecturers could use the Bloom taxonomy to administer class activities with sufficient preparation, while further research might examine how to employ high order thinking skill in various areas.